A Roadmap for Latin America and the Caribbean - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2018)
The International Center for Tropical Agriculture (CIAT), a CGIAR research center operating in Africa, Asia, and Latin America is headquartered in Cali, Colombia. CIAT has worked in collaboration for 50 years with hundreds of partners across Latin America and the Caribbean (LAC). We work with government agencies and other partners on the ground providing tools and scientific and technical support for implementing eco-efficient agriculture at scale. CIAT’s research in LAC helps better understand and harness current and future trends and their links to food security, nutrition, natural resource management, climate change, landscapes, and eco-efficiency in the agri-food sector. Currently active in 14 countries in Latin America and the Caribbean, CIAT plays a valuable role in South-South transfer of agricultural knowledge and learning across the region and globally to accelerate innovation for development impact.